Preparation and characterization of hydrogels from carboxymethyl sago starch and methacrylic acid by electron beam irradiation for controlled-release application - Jamingan, Zakiah (2014)
Carboxymethyl sago starch (CMSS) is one of the natural polymers that have high value as polymeric devices for medical application due to its potential as a biocompatible material. The aims of this project were to prepare and characterize hydrogels for controlled release application, targeted for gastrointestinal route, using CMSS, with the degree of substitution (DS) 0.75, and methacrylic acid (MAA) via electron beam irradiation technique. The hydrogels were prepared by irradiating the CMSS/MAA mixture with electron beam at 5, 10, 15, 20, and 25 kGy doses. Besides, the effect of preparation conditions, such as the amounts of CMSS and MAA added,the irradiation doses on the gel fraction, and the swelling behavior of the hydrogels, were investigated. The hydrogels were then characterized by infrared analysis, thermal properties, surface morphology, and drug release behavior. The study showed that 40% (w/v) of CMSS hydrogels were sufficient for further formulation as controlled release devices. Furthermore, from the study, it had been proven that the optimum amount of 5.0 g or 12.5% of MAA addition gave the highest gel fraction, which was 66.12% and a swelling degree of 94.23 (g/g). The gel fraction also increased with the increase in dose of irradiation. As a matter of fact, the swelling behavior suggested that the hydrogels are pH responsive, whereby minimal swell occurred at pH 2, and optimal swell took place at pH 7. Then, the Fourier Transform Infrared (FTIR) analysis revealed that MAA took part in the formation of CMSS/MAA hydrogels due to the appearance of a new peak at low intensity at 1698 cm-1, which indicated that the MAA was successfully grafted onto the CMSS hydrogel. Furthermore, the thermal analysis results showed that the thermal stability of the hydrogel increased with the addition of MAA into the CMSS hydrogel by shifting the decomposition temperature to a higher temperature, which was 309.1 ºC. In addition, the surface study showed that the morphology of the CMSS/MAA hydrogel was dependent on the amount of MAA. The study is then, extended for controlled release evaluation by using the Bovine Serum Albumin (BSA) as a model drug. The observation showed that hydrogel irradiated at 15 KGy obtained the optimum loaded drug of 44.0 % (w/w) with 88.5 % (w/w) of drug release within 24 hours. In conclusion, this preliminary study suggested that CMSS/MAA hydrogels could be used as a controlled release device for drug released applications.